AB0242 IL6 Genetic Variants and IGA-RF as Markers of Erosiveness at Onset in Early Rheumatoid Arthritis. (15th July 2016) - Canestri, S.; Fedele, A.L.; Tolusso, B.; Petricca, L.; Alivernini, S.; Gigante, M.R.; Gremese, E.; Ferraccioli, G.
Abstract : Objectives: To determine whether genetic variants in the loci of interleukin-6 (IL-6) are associated with clinical and biologic phenotypes of Rheumatoid Arthritis (RA). Methods: Three hundred and forty five early RA (ERA) patients were enrolled in this study (76.2% female; mean age: 54.4±14.1 years; 33.6% VERA). 239 patients (69.3%) were seropositive for at least one antibody: 62.9% ACPA, 48.7% RF -IgM and 33.0% RF-IgA positive, respectively. At diagnosis, 101 subjects (29.3%) had detectable erosions in hands and feet radiographs. All patients were treated according to a tight control strategy (Methotrexate for 3 months, and if an incomplete response was reached after 3 months a combination with Tumor Necrosis Factor (TNF) blockers was started) and at each visit, clinical remission was evaluated according to ACR/EULAR criteria (Felson DT et al. Arthritis Rheum 2011). ERA patients were genotyped for IL6–174G/C polymorphism by PCR and compared with a cohort of healthy subjects (n=293). Results: The frequency of C allele of the IL-6–174G/C SNP was higher in ERA patients (30.7%) compared to healthy controls [23.7%; OR (95%CIs): 1.43 (1.11–1.83)], while the GG genotype was present in 49.6% of ERA and in 59.4% of control subjects [OR (95%CIs): 0.67 (0.49–0.92)] respectively. At baseline, ERA patients carriers of the GG genotype were more likely seropositive compared to patients carrying the C allele [74.9% vs 63.8%, p=0.03], mainly for the IgA-RF positivity [38.6% vs 27.7%; OR (95%CIs): 1.64 (1.04–2.57)]. At diagnosis, IgA-RF positive ERA patients were more likely erosive than IgA-RF negative ones [33.1% vs 25.2%; OR (95%CIs):1.80 (1.11–2.95)]. Conversely, radiographic damage was not associated with gender, symptoms duration, smoking habit, positivity for ACPA or IgM-RF antibodies and disease activity. The percentage of erosive disease increased to 39.6% in ERA patients IgA-RF + carrying the GG genotype compared to the others (24.7%; OR (95%CIs): 2.002 (1.23–3.26)], with a lower presence of radiographic damage in carriers of C allele and IgA-RF negative (12.5%). Finally, patients carrying C allele of IL6–174G/C SNP and IgA- RF negative at diagnosis, were less prone to develop erosions over time than subjects with at least one risk factor (8.0% vs 19.1%, respectively, p=0.02). Conclusions: In our cohort of ERA patients, the presence of C allele of IL6–174G/C SNP associates with RA susceptibility whereas the GG genotype associates with seropositivity for IgA-RF and erosions. These data add new information about the biology underlying the development of radiographic damage in the early phases of RA. Disclosure of Interest: None declared